1997
DOI: 10.1080/03014223.1997.9518104
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and colour differences between subspecies ofSphecophaga vesparum(Hymenoptera: Ichneumonidae)

Abstract: specimens of S. v. hurra, and scored 13 characters. Results showed that the two subspecies could not be reliably discriminated on any morphological characters, but that three colour characters gave >98% separation for females (not including the character originally used to define the subspecies), and seven colour characters gave 100% separation for males. A key for separating the subspecies is presented. A further strain from Israel was examined, and appeared to differ morphologically from the European and Nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Species of parasitoids which were found in nests of D. saxonica in the city of £ód are well known (Schmid-Hempel, 1998). Some of them, especially the parasitic wasp Sphecophaga vesparum, of which a few subspe-cies are known (Berry et al 1997), have been successfully used against species of wasps, which are considered as invasive species, especially German wasp (Vespula germanica) and the common wasp (V. vulgaris), and the presence of which has become a serious problem for the residents in New Zealand (Barlow et al 1996, Harris & Read 1999. This ichneumonid has been recorded in Poland in the nests of D. saxonica in some areas, for example Borecka Primeval Forest (Pawlikowski & Pawlikowski 2003), Kampinoska Primeval Forest (Sawoniewicz & Winiowski 2007) and in the city of £ód (Nadolski 2004).…”
Section: Accompanying Fauna Of Wasp Nestsmentioning
confidence: 99%
“…Species of parasitoids which were found in nests of D. saxonica in the city of £ód are well known (Schmid-Hempel, 1998). Some of them, especially the parasitic wasp Sphecophaga vesparum, of which a few subspe-cies are known (Berry et al 1997), have been successfully used against species of wasps, which are considered as invasive species, especially German wasp (Vespula germanica) and the common wasp (V. vulgaris), and the presence of which has become a serious problem for the residents in New Zealand (Barlow et al 1996, Harris & Read 1999. This ichneumonid has been recorded in Poland in the nests of D. saxonica in some areas, for example Borecka Primeval Forest (Pawlikowski & Pawlikowski 2003), Kampinoska Primeval Forest (Sawoniewicz & Winiowski 2007) and in the city of £ód (Nadolski 2004).…”
Section: Accompanying Fauna Of Wasp Nestsmentioning
confidence: 99%
“…Instead, there is a continuous gradient of parasitoid sizes, principally determined by nutritional intake. Berry et al (1997) also showed that the distribution of wing-lengths of adults from white and yellow cocoons formed a continuous gradient from fully winged to brachypterous forms.…”
Section: Discussionmentioning
confidence: 96%
“…Most species of Sphecophagina for which host records are known are ectoparasitoids of vespine wasps (Sonan 1937;Townes and Townes 1962;Townes 1970;Richards 1978;Makino 1983Makino , 1989Chiu et al 1984;Sayama and Konishi 1996;Berry et al 1997;Konishi et al 1997). Sphecophaga vesparum, in particular, was introduced as a possible biological control agent against Vespula germanica (F.) and V. vulgaris (L.) in New Zealand (Donovan and Read 1987;Beggs et al 1996Beggs et al , 2002Barlow et al 1998;Harris and Rose 1999;Donovan et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Many species of Sphecophagina have two seasonal forms, an overwintering form and a summer form (Townes and Townes 1962;Makino 1983;Horstmann 1987;Donovan 1991Donovan , 2002Berry et al 1997;Konishi et al 1997;Lee and Oh 2006). They are sometimes treated as two different species or subspecies, based on external characteristics and color patterns (Townes and Townes 1962).…”
Section: Introductionmentioning
confidence: 99%